2018
DOI: 10.1002/cjce.23138
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnetic field on the ammonia‐based CO2 absorption process

Abstract: The performance of ammonia‐based CO2 absorption under static magnetic field conditions was discussed. The removal efficiency of CO2, CO2 load, and absorption capacities were studied using a bubble reactor system. The CO2 removal efficiencies, CO2 load, and absorption capacity under static magnetic field conditions were calculated at four kinds of different operating conditions, which included CO2 concentration in flue gas, gas flow rate, concentrations of aqueous ammonia, and reaction temperature. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…They applied both an electric and magnetic field, parallel or perpendicular to the linker direction of the GOF and reported that there was no significant change in the GOF to CO 2 adsorption by a magnetic field. Another study by Zhang et al [36] presented the performance of ammonia-based CO 2 adsorption under static magnetic field conditions, where the adsorption capacities were studied by a bubble reactor system. When comparing the absorption of CO 2 under static magnetic field conditions and no magnetic field conditions, it was found that under the magnetic field, the absorption capacity of CO 2 and the removal efficiency of CO 2 were enhanced in ammonia-based sorbents.…”
Section: Introductionmentioning
confidence: 99%
“…They applied both an electric and magnetic field, parallel or perpendicular to the linker direction of the GOF and reported that there was no significant change in the GOF to CO 2 adsorption by a magnetic field. Another study by Zhang et al [36] presented the performance of ammonia-based CO 2 adsorption under static magnetic field conditions, where the adsorption capacities were studied by a bubble reactor system. When comparing the absorption of CO 2 under static magnetic field conditions and no magnetic field conditions, it was found that under the magnetic field, the absorption capacity of CO 2 and the removal efficiency of CO 2 were enhanced in ammonia-based sorbents.…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 capture using nanofluids has been proposed to improve absorption efficiency, and higher efficiency leads to lower energy consumption. [ 6–10 ]…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 capture using nanofluids has been proposed to improve absorption efficiency, and higher efficiency leads to lower energy consumption. [6][7][8][9][10] There have been several studies on mass transfer enhancement in absorption processes using nanoparticles in water as it is a readily available, inexpensive, and biocompatible base fluid. [10][11][12][13][14][15][16][17][18][19][20][21] Esmaeili Faraj et al [22] studied H 2 S absorption with a water-nanofluid mixture using exfoliated graphene oxide (EGO) nanoparticles in a bubble column.…”
Section: Introductionmentioning
confidence: 99%